Diseño para todos - Jiménez-González, Daniel (Instituto Tecnológico de Costa Rica., 2019)
Nowadays, Costa Rica experiences an increase in both its senior and disabled population. Consequently, an obligation to cover the new needs of these citizens emerges. Arquitechture must act as a brigde to link all knowledge in favor of a sustainable development and articulated spaces aiming to solve the needs of people in the future. This must be done based on the principles of inclusion and equality in which everyone can have access to the same opportunities. In this line, this dissertation project has its foundations in the elements and proposals presented by the Diseño para Todos. Following its parameters, thinking about serving the present and upcoming demands, the communal necessities, and the inexistent community social equipment, an arquitectonic proposal was formulated for the community integral center in El Edén, located in Purral, Goicoechea.
propuesta arquitectónica del Centro Integral Comunitario
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: Diseño arquitectónico; Centros comunitarios